2021
DOI: 10.1371/journal.pone.0250019
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screening of the ReFRAME, Pandemic Box, and COVID Box drug repurposing libraries against SARS-CoV-2 nsp15 endoribonuclease to identify small-molecule inhibitors of viral activity

Abstract: SARS-CoV-2 has caused a global pandemic, and has taken over 1.7 million lives as of mid-December, 2020. Although great progress has been made in the development of effective countermeasures, with several pharmaceutical companies approved or poised to deliver vaccines to market, there is still an unmet need of essential antiviral drugs with therapeutic impact for the treatment of moderate-to-severe COVID-19. Towards this goal, a high-throughput assay was used to screen SARS-CoV-2 nsp15 uracil-dependent endonucl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Gemcitabine and cidofovir were reported to inhibit SARS-CoV and SARS-CoV-2 proteins with IC 50 values of 4.95 µM and 36 µM [54,55]. Further, telbivudine, tipiracil, cytarabine, and citicoline were recommended as 3CL pro inhibitors [56][57][58][59][60][61]. This transitory literature scanning confirms these pharmaceuticals' activity against 3CL pro of SARS-CoV-2, as demonstrated in the present study.…”
Section: The Binding Free Energiessupporting
confidence: 86%
“…Gemcitabine and cidofovir were reported to inhibit SARS-CoV and SARS-CoV-2 proteins with IC 50 values of 4.95 µM and 36 µM [54,55]. Further, telbivudine, tipiracil, cytarabine, and citicoline were recommended as 3CL pro inhibitors [56][57][58][59][60][61]. This transitory literature scanning confirms these pharmaceuticals' activity against 3CL pro of SARS-CoV-2, as demonstrated in the present study.…”
Section: The Binding Free Energiessupporting
confidence: 86%
“…Of these, functional groups of Compound IV share analogous interactions with Nsp15 in Pocket A/B with those of the compound of pose 4 that shows the lowest . Choi et al used high-throughput assay to screen compounds against Nsp15, and inhibition was confirmed for three hits in vitro and showed that Exebryl-1 (ß-amyloid anti-aggregation molecule for Alzheimer’s therapy) has antiviral activity 38 . They also showed that the most plausible binding residues with Exebryl-1 significantly overlap with those of Pocket B. Interestingly, the compounds that we found by AutoDock Vina shares some similarity in functional groups with Exebryl-1.…”
Section: Resultsmentioning
confidence: 99%
“…In this direction, Benzopurpurin B and Congo red were shown to display the higher inhibition on Nsp15 activity. In addition, these drugs reduced the infectivity of the SARS-CoV in Vero cells [ 123 ]. Based on this evidence, a more comprehensive investigation is needed for the exploitation of RNAse A inhibitors as drugs that can target Nsp15 activity.…”
Section: Drugs Targeting Nsp15 and Nsp16 Proteinsmentioning
confidence: 99%
“…Using the available crystallographic data for NSP15 from MERS, SARS-CoV, and SARS-CoV-2, several groups have employed virtual screening, molecular docking, and molecular dynamic simulation techniques to identify putative antivirals against Nsp15 [ 123 , 124 ]. Nsp15 is a uridine-specific endoribonuclease and amino acid residue Ser294 has been proposed to play a crucial role in uracil recognition in the catalytic pocket [ 75 ].…”
Section: Drugs Targeting Nsp15 and Nsp16 Proteinsmentioning
confidence: 99%